Causes of Accidents Involving Scaffolding at Construction Sites - Abas, Nor Haslinda; Noridan, Muhammad Ridhwan; Rahmat, Muhamad Hanafi; Abas, Nor Ain; Ibrahim, Nur Qamarina (UTHM Publisher, 2020)
Fatal accidents related to the use of scaffolds are one of the most common types of fatal accidents at construction sites in Malaysia, as reported by the Department of Occupational Safety and Health (DOSH). Therefore, the purpose of this study is to investigate the main causes of accidents involving scaffolding at construction sites, based on the perceptions of safety personnel. This study involved collecting data by distributing questionnaires to safety personnel working at construction sites in Johor. Data were analyzed using the Average Min Index and Relative Importance Index (RII). From these studies, the main causes of scaffolding accidents are ignoring safety rules, improper inspections, and improper foundation/stability. The findings of this study provide knowledge and awareness of the causes or factors of scaffolding accidents at construction sites and serve as a reference to construction employers in understanding the factors contributing to scaffolding accidents.